MANAJEMEN PENGETAHUAN DALAM ORGANISASI YANG DIDORONG OLEH AI: MENINGKATKAN INOVASI DAN KEUNGGULAN KOMPETITIF - K. M. Faisal Reza; M. Fakhriansyah; Dimas Ardiansyah (Berajah Journal, 2026)
The development of artificial intelligence has driven organizational transformation in managing knowledge as a strategic asset that determines the sustainability of innovation and competitive advantage. AI-based organizations are not only required to adopt advanced technology but also to be able to effectively integrate the processes of creating, storing, sharing, and utilizing knowledge. This study aims to analyze the role of knowledge management in increasing innovation capacity and strengthening competitive advantage in organizations implementing AI. The study uses a literature review approach by examining various scientific articles, books, and relevant academic publications on knowledge management, artificial intelligence, organizational innovation, and competitive advantage. The results of the study indicate that the integration of knowledge management with AI technology can improve decision-making efficiency, accelerate the innovation process, strengthen organizational learning, and support adaptation to the dynamics of an increasingly complex business environment. In addition, the successful implementation of knowledge management in AI-based organizations is influenced by organizational culture, human resource readiness, digital infrastructure, and effective data governance. Thus, knowledge management plays a strategic foundation that enables organizations to maximize the potential of AI to create sustainable added value and maintain competitiveness in the era of digital transformation.